Does green infrastructure work? Precipitation, protected areas, floods and landslides - Juan David Robalino; Katrina Mullan; Matías Piaggio; Marisol Guzmán (Inter-American Development Bank (IDB), 2023)
We evaluate whether floods and landslides are more likely when rain falls inside versus outside protected areas (PAs). We use monthly municipality data for the period 2000-2015 in Guatemala and monthly district data for the period 1992-2019 in Costa Rica. We define relevant catchment areas using water flows to population centers of administrative units. Then, we calculate the precipitation inside and outside PAs within the relevant catchment areas, and test how the frequency of floods and landslides is affected by whether rain falls inside or outside PAs. We use a two-way fixed effect panel data model. For Guatemala, we find no robust statistically significant effects on these types of disasters. However, in Costa Rica, we find that shifts in precipitation towards PAs reduce floods significantly. These results were highly robust. We also find effects on landslides in densely populated districts, as well as reductions in flood-related deaths.
Keywords: Q54; Q28; Q24; 330; Disasters; Floods; Landslides; Protected areas; Precipitation